القواعد الفقهية المتعلقة بإنفاق المال الحرام في الأعمال الخيرية: دراسة تطبيقية - إدريس، محمود عمر محمد علي (جامعة الأميرة نورة بنت عبد الرحمن, 2024)
يعد المال ضرورة من ضرورات الحياة فلا يستقيم ميزانها إلا بوجوده ويختل قوامها بفقده، فهو من الضروريات الخمس التي هي: حفظ الدين، والنفس، والنسل، والمال، والعقل، والإخلال بهذا المقصد يعد إخلالا بالمقاصد الأخرى، فعلم بهذا مكانة المال في الإسلام وضرورته لاستقامة الحياة. وفي هذه الدراسة حصر واستقراء للقواعد الفقهية المتعلقة بإنفاق المال الحرام في الأعمال الخيرية، ويشمل ذلك القواعد الفقهية المتعلقة بإنفاق المال المحرم لعينه، والقواعد الفقهية المتعلقة بإنفاق المال المحرم لكسبه، والقواعد الفقهية المعلقة بإنفاق المال المختلط بالحرام، والتطبيق عليها من المسائل الفقهية المعاصرة التي تندرج تحت هذه القواعد، وتوضيح الصورة الصحيحة للمصادر المالية لمؤسسات العمل الخيري بإرجاع المسائل الفرعية لقواعدها الكلية ووضع الحلول المناسبة للأموال التي ترد إلى تلك المؤسسات بعرضها على ميزان الشرع لبيان الجائز والممنوع منها، وبيان حكم التبرع بتلك الأموال سواء كانت من الأموال المحرمة لذاتها، كالخمر والميسر، أو المحرمة لكسبها أي لوصف خارج عن حقيقتها كالأموال المغصوبة والمكتسبة من الربا ونحوها، أو الأموال المشبوهة أو المختلطة بالمحرم مثل أسهم بعض الشركات المساهمة في عصرنا الحالي لبيان المعايير والضوابط الشرعية الخاصة بهذه المسائل مع بيان الحلول المناسبة لمعضلاتها، وختم البحث بأهم النتائج والتوصيات، ثم فهارس المصادر والمراجع العلمية. Money is considered a necessity of life, and its balance is not maintained without its presence, while its equilibrium is disrupted by its loss. It is one of the five necessities, which are: preserving religion, life, progeny, wealth, and intellect. Disturbing this objective is considered a disruption of the other objectives. Thus, the importance of wealth in Islam and its necessity for a righteous life is well-established. In this study, there is an enumeration and exploration of the jurisprudential principles related to spending illicit wealth in charitable activities. This includes principles related to spending illicit wealth as it is, principles related to spending illicitly earned wealth, and principles related to spending wealth that is mixed with the illicit. The study also applies these principles to contemporary jurisprudential issues falling under these categories. It elucidates the correct understanding of the financial sources for charitable institutions, referring subsidiary issues back to their general principles, and proposes appropriate solutions for funds returned to these institutions. The study also examines these funds under the scrutiny of Sharia, distinguishing between permissible and forbidden aspects. It also clarifies the ruling on donating such funds, whether they are inherently forbidden, like alcohol and gambling, or earned illicitly, such as embezzled funds and those gained through usury. The study also addresses funds with suspicious or mixed origins, like shares in some current joint-stock companies. It presents the Sharia standards and guidelines for these issues along with appropriate solutions for their dilemmas. The research concludes with key findings and recommendations, followed by indices of sources and scientific references.
Keywords: الفقه الإسلامي -- القواعد الفقهية -- أحكام المال الحرام -- الأنشطة الخيرية